Can The Poverty Status of a Household be Influenced by Age? Susenas Data for North Lampung Regency, 2022 - Rindi Mustika Roslaini; Dedy Yuliawan (International Journal of Economics, Business and Innovation Research, 2024)
This study focused on the poverty status of households in North Lampung Regency in 2022. It used a quantitative research method using primary data obtained from the Badan Pusat Statistik (BPS). The data used is from the national socio-economic survey, with a population and sample size of 735 households. This study sought to ascertain the impact of gender, age, and household size on the poverty status of households. In this study, logistic regression was employed, and the Odds Ratio value was utilized to compare the population's proportion in one category to that in another for the independent variables that affected the dependent variable. The findings of this study show that household size had a substantial impact on household poverty status but that age and gender had no discernible impact.